Implementation of Incentive Income Tax Article 22 to Business Sector Affected by Covid-19 (Case Study PT STI) - Sumarno Manrejo; Putwi Firdayanti (Perbanas Institute, 2022)
The purpose of this study is to determine the implementation of withholding tax Article 22 Incentive including the calculation, payment, reporting, and its impact on the business sector affected by Covid-19. The object of this research is a Japanese company located in Jakarta. The data used in this study were obtained from financial reports, and data related to imports for one year from October 1, 2019, to September 30, 2020. The research method used in this study is a qualitative method. The results of the study revealed that the company chose to take advantage of the import tax income article 22 exemption incentive, in the process the company had followed the applicable policy, but in the process of depositing and utilizing this import tax income article 22 incentive, the company made a technical error, so that for one tax period of a month the company did not get tax income article 22 import incentives. While the effect on the 2020 Annual Corporate Income Tax Return is underpaid, when viewed from the process carried out by the company and seen from the company's compliance indicators, it can be categorized as a compliant taxpayer even though the documentation and company discipline is still insufficient.